Homo antecessor: The state of the art eighteen years later. (17th March 2017) - Bermúdez-de-Castro, José-María; Martinón-Torres, María; Martín-Francés, Laura; Modesto-Mata, Mario; Martínez-de-Pinillos, Marina; García, Cecilia; Carbonell, Eudald
Abstract: It is eighteen years since the human fossils recovered from the TD6 level of the Gran Dolina cave site, in Sierra de Atapuerca (Burgos, northern Spain) were assigned to a new hominin species, Homo antecessor . This review summarizes the main results obtained from the study of these fossils during this period. The increase of the African and Eurasian fossil record, as well as the application of new methodological approaches, has led to competing interpretations about its hypothetical phylogenetic position and possible evolutionary scenarios. At present, we can argue that this species is defined by a unique mosaic of primitive traits for the Homo clade, a certain number of derived features present in modern humans, a significant suite of derived features shared with Neandertals and their ancestors in the European Middle Pleistocene (in particular with the Atapuerca-Sima de los Huesos hominins), and some derived features shared with the Chinese Middle Pleistocene hominins. From this evidence, we suggest that a speciation event could have occurred in Africa/Western Eurasia, originating a new Homo clade. Homo antecessor, most probably dated to the MIS 21, could be a side branch of this clade placed at the westernmost region of the Eurasian continent.